Directional transmission of acoustic wave based on sector-shaped structure - Cai, Wentao; Zhao, Xinsa; Hao, Guodong; Han, Jianning (AIP advances, 2025)
In this paper, three kinds of protocell models were constructed by modulating the steering using a sector structure of the same size, and the artificial acoustic periodic structure was obtained by the array protocell model. At a specific incident frequency, although there are a large number of scatterers, the sound waves do not scatter randomly but can be transmitted directionally along a pre-designed channel, thus achieving the quantum spin Hall effect in acoustics. This structure exhibits broadband characteristics and demonstrates similar directional transmission characteristics at incident frequencies of 127–137 kHz. However, due to the variation in the incident frequency of the sound waves, the wavelength of the incident waves changes accordingly, resulting in different transmission efficiencies. It is found that the incident wavelength of 131 kHz has the best matching coupling characteristics with the structure so as to reduce the acoustic energy loss caused by impedance mismatch. In addition, the sector-shaped acoustic directional transmission model is subject to spin locking, and the channels at different interfaces have different spin locking characteristics. This also provides multiple adjustable degrees of freedom for the directional propagation of sound waves. This research provides new design insights and potential applications for acoustic communication and quantum acoustics.